Kerentanan Buruh Perempuan dalam Menjalankan Fungsi Keluarga - Natalia A.I. Barage; Rupita Rupita; Syarifah Ema Rahmaniah; Diaz Restu Darmawan (Prodi Sosiologi FISIP Universitas Teuku Umar, 2023)
This paper examines the social vulnerability that occurs to female workers at PT. Sintang Argo Mandiri in Sintang district. Through descriptive qualitative methods, this paper is able to describe how the forms of social vulnerability that occur in women workers and find out the causes of social vulnerability based on the results of interviews with women workers in oil palm companies. One of the key informants in this paper is the village head of Lengkenat. The results of the study found several forms of vulnerability that occurred in women workers such as marginalization. The form of vulnerability is in the form of lack of health insurance for female workers, double workload, and illegal levies between fellow employees. In addition, it was also found that the factors causing social vulnerability include internal factors such as age, low education level, and individual willingness to work. While external factors are women who experience economic difficulties, large number of family dependents, low husband's income, and wages from the company sector concerned.